A visualization analysis of research on arterial compression hemostatic devices using VOSviewer and CiteSpace - Liu, Li; Xiong, Juan; Xu, Jianmei; Tu, Ping (Frontiers in Neurology, 2025)
BackgroundCardiovascular and cerebrovascular diseases pose a significant health challenge in modern society, with the advancement of interventional therapy and vascular intervention technology playing crucial roles. In the context of post-interventional procedures, the application of suitable pressure at the puncture site is of utmost importance for achieving hemostasis. A variety of arterial compression devices are utilized in clinical settings to facilitate this critical step. A bibliometric analysis is used to assess the impact of research in a particular field. This study seeks to explore the research trends, key themes, and future directions of arterial compression hemostatic devices in international scholarly literature to inform future research endeavors.MethodsEnglish-language literature on arterial compression hemostatic devices was systematically retrieved from the Web of Science (WOS) and Scopus databases until December 31, 2024. In this study, we employed VOSviewer 1.6.18 and CiteSpace 6.2.r4 to systematically analyze a comprehensive set of parameters, which included authorship and institutional affiliations, geographical distribution by country, and thematic categorization through keywords.ResultsIn total, 4,358 relevant publications were retrieved. This study’s results section highlights a growing body of research on arterial compression hemostasis devices, with a significant increase in publications post-2000, reaching 107 in 2022. Department of Cardiology leads in institutional contributions, while ‘Bernat, lvo’ is the most prolific authors. Keyword analysis identifies “human,” “article,” “hemostasis,” “female,” and “male” as key terms, with 7 thematic clusters revealed by hierarchical clustering.ConclusionThe results provide an overview of research on arterial compression hemostatic devices, which may help researchers better understand classical research, historical developments, and new discoveries, as well as providing ideas for future research.